(untitled) (Global Journal of Science Frontier Research, 2023)
Different vertices are colored in a plan Adjacent vertices are colored differently from nonadjacent vertices which are colored the same color One color is used for a single point two color are used for points without a loop and a maximum of four color are used for points with a loop A maximum of four color are used to color all points